The Finite Element Analysis Program MSC Marc/Mentat A First Introduction - Öchsner, Andreas; Öchsner, Marco; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
Based on simple examples, this book offers a short introduction to the general-purpose finite element program MSC Marc, a specialized program for non-linear problems (implicit solver) distributed by the MSC Software Corporation, which is commonly used in academia and industry. Today the documentation of all finite element programs includes a variety of step-by-step examples of differing complexity, and in addition, all software companies offer professional workshops on different topics. As such, rather than competing with these, the book focuses on providing simple examples, often single-element problems, which can easily be related to the theory that is discussed in finite element lectures. This makes it an ideal companion book to classical introductory courses on the finite element method.
Introduction to Marc/Mentat -- Rods and Trusses -- Euler-Bernoulli Beams and Frames -- Timoshenko Beams -- Plane Elements -- Classical Plate Elements -- Three-Dimensional Elements -- Elasto-Plastic Simulation -- Advanced Topics -- Answers to Additional Questions.
Keywords: Mechanics, Applied; Solids; Computer-aided engineering; Materials -- Analysis; Solid Mechanics; Computer-Aided Engineering (CAD, CAE) and Design; Characterization and Analytical Technique